ASK120067 potently suppresses B-cell or T-cell malignancies in vitro and in vivo by inhibiting BTK and ITK - Song, Peiran; Bai, Gang; Chan, Shingpan; Zhang, Tao; Tong, Linjiang; Su, Yi; Shen, Yanyan; Chen, Yi; Liu, Yingqiang; Lai, Mengzhen; Ning, Yi; Tang, Haotian; et al. (Frontiers in Pharmacology, 2022)
Hyperactivation of Bruton’s tyrosine kinase (BTK) or interleukin-2-inducible T cell kinase (ITK) has been attributed to the pathogenesis of B-cell lymphoma or T-cell leukemia, respectively, which suggests that BTK and ITK are critical targets for the treatment of hematological malignancies. We identified a novel third-generation epidermal growth factor receptor (EGFR) inhibitor, ASK120067 (limertinib) in our previous research, which has been applied as a new drug application against non-small cell lung cancer in China. In this work, we found that ASK120067 displayed potent in vitro inhibitory efficacy against BTK protein and ITK protein via covalent binding. In cell-based assays, ASK120067 dose-dependently suppressed BTK phosphorylation and exhibited anti-proliferation potency by inducing apoptosis in numerous B-lymphoma cells. Meanwhile, it caused growth arrest and induced the apoptosis of T-cell leukemia cells by attenuating ITK activation. Oral administration of ASK120067 led to significant tumor regression in B-cell lymphoma and T-cell leukemia xenograft models by weakening BTK and ITK signaling, respectively. Taken together, our studies demonstrated that ASK120067 exerted preclinical anti-tumor activities against B-/T-cell malignancy by targeting BTK/ITK.